REFORMULASI DARI SOLUSI 3-SOLITON UNTUK PERSAMAAN KORTEWEG-de VRIES - mustikaningsih, Dian; sutimin, sutimin (MATEMATIKA, 2002)
The solution ofÂ 3-soliton for Korteweg-de Vries (KdV) equation can be obtained by the Hirota Method. The reformulation of the 3-soliton solution was represented as the superposition of the solution of each individual soliton. Moreover, the asymptotic form of 3-soliton solution was obtained by limiting of the t parameter. The phase shift of each individual soliton are analysed in detail based its asymptotic form. The results of the analysis shown that the first soliton always have a phase shift called forward, the second soliton have some possibility (there is no phase shift, have aÂ forward phase shift, or have a backward phase shift), and for the third soliton always have a phase shift called backward.